Construction of a lactate-related prognostic signature for predicting prognosis after surgical repair for acute type a aortic dissection - Wang, Zhigang; Li, Kai; Xu, Jingfang; Cheng, Xiaofeng; Wang, Dongjin (Frontiers in Physiology, 2022)
Background: Serum lactate is commonly measured in the perioperative period in patients who have undergone surgery for an acute type A aortic dissection (ATAAD). However, conflicting data has been reported as to whether lactate elevation is associated with short-term prognosis. The aim of the current study was to determine the association between perioperative arterial lactate levels and postoperative 30-day mortality. Methods: Patients who underwent repair of a ATAAD at our institution were retrospectively screened and those with comprehensive measurements of serum lactate before surgery and at 0, 1, 3, 6, 12, and 24 h after surgery in the intensive care unit (ICU) were selected for the analysis. Patients’ demographic features and outcomes were reviewed to determine risk factors associated with 30-day mortality using logistic regression modeling. The association between serum lactate levels at different time points and 30-day mortality were analyzed by receiver-operating characteristic curves. Results: 513 patients were identified and retrospectively analyzed for this study including 66 patients (12.9%) who died within 30 days after surgery. Patients who died within 30 days after surgery had elevated lactate levels measured before surgery and at 0, 1, 3, 6, 12, and 24 h after their ICU stay. Lactate measured at 24 h post ICU admission (odds ratio, 2.131; 95% confidence interval, 1.346–3.374; p = 0.001) was a predictor of 30-day mortality. The area under the curve (AUC) for 30-day mortality with lactate levels at 12 h and 24 h post ICU stay were 0.820 and 0.805, respectively. Conclusion: Early elevation of lactate level is correlated with increased 30-day mortality in patients who received ATAAD surgical repair.